The Encyclopedia of Television, Cable, and Video - Reed, R.M. author. aut Link
640 p.
Keywords: This is a major reference work about the overlapping fields of television, cable and video. With both technical and popular appeal, this book covers the following areas: advertising, agencies, associations, companies, unions, broadcasting, cable-casting, engineering, events, general production and programming.